Independent Ancient Polyploidy Events in the Sister Families Brassicaceae and Cleomaceae - Schranz, M. Eric (American Society of Plant Biologists, 2006)
Recent studies have elucidated the ancient polyploid history of the Arabidopsis thaliana (Brassicaceae) genome. The studies concur that there was at least one polyploidy event occurring some 14.5 to 86 million years ago (Mya), possibly near the divergence of the Brassicaceae from its sister family, Cleomaceae. Using a comparative genomics approach, we asked whether this polyploidy event was unique to members of the Brassicaceae, shared with the Cleomaceae, or an independent polyploidy event in each lineage. We isolated and sequenced three genomic regions from diploid Cleome spinosa (Cleomaceae) that are each homoeologous to a duplicated region shared between At3 and At5, centered on the paralogs of SEPALLATA (SEP) and CONSTANS (CO). Phylogenetic reconstructions and analysis of synonymous substitution rates support the hypothesis that a genomic triplication in Cleome occurred independently of and more recently than the duplication event in the Brassicaceae. There is a strong correlation in the copy number (single versus duplicate) of individual genes, suggesting functionally consistent influences operating on gene copy number in these two independently evolving lineages. However, the amount of gene loss in Cleome is greater than in Arabidopsis. The genome of C. spinosa is only 1.9 times the size of A. thaliana, enabling comparative genome analysis of separate but related polyploidy events.